(untitled) (Experimental biology, 2020)
The production and development of active probiotic drugs against a number of pathogens are gaining relevance, along with the global trend of abandoning the use of traditional antibiotic drugs in food production. The reason is the increase in antibiotic resistance, in particular, was observed in such pathogenic test strains as: Escherichia coli, Staphylococcus aureus, Listeria monocytogenes, Salmonella typhi. Among the most common representatives of lactic acid bacteria of shubat and camel milk can be found: Enterococcus spp., Lactococcus spp., Lactobacillus spp., Leuconostoc spp. These types of microorganisms have functional probiotic properties, which can be used in the development of a probiotic preparation for farm animals and birds. The article presents the results of a study of the functional probiotic properties of lactobacillus camel milk and data on the possible use of these strains in poultry farming. Methods for assessing probiotic potential are described, including: the ability to survive in an aggressive environment of the digestive tract, the study of antagonistic activity, adhesion and synthesis of biologically active substances. The study of this topic is relevant and has wide possibilities of application in the production of veterinary probiotic preparations in order to minimize and reject antibiotic substances as growth factors and counteract bacterial diseases of animals.